Efeitos do ácido p-metoxicinâmico em raízes de Euphorbia heterophylla - Moreira-Vilar, Flávia Carolina (2016)
Natural compounds with allelopathic action can serve as a basis for the development of products that will assist in crops management, particulary regard to weeds. Therefore, the aim of this work present below was to evaluate the effects of p-methoxycinnamic acid (MCA) on Euphorbia heterophylla roots in the young stage. The resuls indicate that allelopathic effect of MCA has significantly reduced growth rate on roots at low concentrations, reaching 50% inhibition with 47.67 μM and 190 μM to 80% inhibition. It was also possible to observe a gradual reduction of cell division with increasing concentration as well a loss of cell viability on the roots apices exposed to MCA. However, the amount of amino acids was increased with acid concentration addition. There was an increase of ferulic acid, cumaric acid and incorporation of MCA on the cell wall. The activation of cell wall peroxidase suggest its participation on esterification process of this components. The monomers concentration was not affect and only I80increase PAL activity and lignin content. Root apex respiratory was also affected by MCA. The allelochemical increased the extramitochondrial respiration, induced the hydrogen peroxide accumulation and activated enzymes of antioxidative metabolism. ATP/ADP rate was reduced in all treatment tested.